Head and neck cancer: from anatomy to biology. Issue 9 (29th March 2013) - Bose, Pinaki; Brockton, Nigel T.; Dort, Joseph C.
Abstract : The 20th century saw great advances in anatomy‐based (surgery and radiotherapy) and chemotherapy approaches for treating head and neck squamous cell carcinoma (HNSCC) and improving quality of life (QoL). However, despite these advances, the survival rate in HNSCC remains at ∼50%. Front‐line treatments often cause severe toxicity and debilitating long‐term impacts on QoL. In recent decades, dramatic advances have been made in our knowledge of fundamental tumor biology and signaling pathways that contribute to oncogenesis and cancer progression. These insights are presenting unprecedented opportunities to develop more effective and less toxic treatments that are specific to particular molecular targets. This review discusses some of the major, potentially targetable, molecular pathways associated with head and neck carcinogenesis. We present the general mechanism underlying the functional components for each signaling pathway, discuss how these components are aberrantly regulated in HNSCC and describe their potential as therapeutic targets. We have restricted our discussion to "drug‐able targets" such as oncogenes including those associated with HPV, tumor hypoxia and microRNAs and present these changes in the context of HNSCC patient care. The specific targeting of these pathways to achieve cancer control/remission and reduce toxicity is now challenging conventional treatment paradigms in HNSCC. This new "biologic era" is transforming our ability to target causal pathways and improve survival outcomes in HNSCC.